Publication Ethics Policies for Journal of Advances in Internal Medicine (JAIM) - Editor, The (Journal of Advances in Internal Medicine, 2013)
DOI: http://dx.doi.org/10.3126/jaim.v2i2.8784 Journal of Advances in Internal Medicine 2013;02(02)